The Influence of Social Media, Packaging, and Online Customer Reviews on The Purchase Decision of Local Perfume Brand HMNS - Dhea Ayu Cahyaningsih; Edwin Zusrony; Myra Andriana (ITB AAS Indonesia Surakarta, 2025)
This study examines the influence of social media, packaging, and online customer evaluations on the purchasing decisions for the local perfume HNMS. The study population comprises Generation Z consumers of the local perfume brand HNMS, with a sample size of 100 respondents selected by the Accidental Sampling method and the Lemeshow formula. The primary data analyzed was obtained through a questionnaire. Utilizing SPSS version 30.0 for data processing, the findings indicate that all question item indicators of the study instrument are valid and all variables are dependable. According to the simultaneous test, all independent variables influence purchasing decisions. The regression coefficient and t-test results indicate that social media, packaging, and online feedback from consumers exert a positive and significant influence on purchasing decisions. The online customer review variable exhibits the most significant impact, evidenced by the highest t-count value.